Kasih Sebagai Solusi Permasalahan Keadilan - Setiawan, Hendro; Wibowo, Andreas (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2025)
This research is aimed at finding the root of the problem behind the situation of serious injustice that occurs in the world today. The most surprising fact is that the 20th century, and continuing into the 21st century, has created the most unequal or unjust society in human history. Social inequality occurs massively both at the level between countries and between individuals. The research method used is literature study. Research is carried out by studying from the literature the concepts of justice that are practiced in today's world, and then looking for weaknesses in these concepts. Try to examine and compare the existing weaknesses with the teachings of Christianity to reach a conclusion. This research succeeded in showing that Christian religious teachings about love are an element needed to cover the weaknesses of the prevailing concepts of justice. The conclusion that this research produces is that Christian teachings about love are very relevant in improving world justice.